Probability and statistics with reliability, queuing, and computer science applications - Trivedi, Kishor Shridharbhai, 1946- 4 0 16; 5 (Englewood Cliffs, NJ : Prentice-Hall, 1982)
An introduction to probability, stochastic processes, and statistics for college students.
Includes indexes.
Bibliography: p. 573-578.
Booklist
Young Adult;Young Adult
Keywords: 2 -- 0; 6; Data processing.;Data processing.;Data processing.;Data processing. -- Probabilities;Mathematical statistics;Computer algorithms.;Probabilities;Statistics; 20; 2